1990
DOI: 10.1038/348448a0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence equating SRY and the testis-determining factor

Abstract: The testis-determining factor gene (TDF) lies on the Y chromosome and is responsible for initiating male sex determination. SRY is a gene located in the sex-determining region of the human and mouse Y chromosomes and has many of the properties expected for TDF. Sex reversal in XY females results from the failure of the testis determination or differentiation pathways. Some XY females, with gonadal dysgenesis, have lost the sex-determining region from the Y chromosome by terminal exchange between the sex chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
374
2
25

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 893 publications
(407 citation statements)
references
References 13 publications
6
374
2
25
Order By: Relevance
“…In 1990, researchers made headlines when they uncovered the identity of this gene 3,4 , which they called SRY. Just by itself, this gene can switch the gonad from ovarian to testicular development.…”
Section: Sex Redefinedmentioning
confidence: 99%
“…In 1990, researchers made headlines when they uncovered the identity of this gene 3,4 , which they called SRY. Just by itself, this gene can switch the gonad from ovarian to testicular development.…”
Section: Sex Redefinedmentioning
confidence: 99%
“…The sex-determining region of Y chromosome (SRY) is the PY53.2 section on the Yp, about 2.1 kb, nears the pseudoautosomal region. Sinclair et al discovered the SRY in 1990 and they considered that SRY is the best candidate gene for the TDF [14]. Lots of studies have shown that the proteins encoded by the SRY gene play a crucial role in sex determination and differentiation [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The entire open reading frame of the sexdetermining region Y (SRY) gene was amplified and directly sequenced as described (2,3).…”
Section: Molecular Analysis Maternity Testing Was Performed By Usingmentioning
confidence: 99%
“…Normal sexual differentiation in 46,XY individuals relies on a complex cascade of numerous genes, many of which have yet to be identified (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Defects in these genes can cause disorders of sexual development of varying severity.…”
Section: Introductionmentioning
confidence: 99%